Filtration and optimization for the recovery of powder soap used in wire drawing process - Eren, Orhan; Benlice, Esra; Duran, Ali; Yılmaz, Erkan (Afyon Kocatepe Üniversitesi)
Today, the amount of production and production-related waste has increased in order to meet the rapidly increasing consumption. Recycling processes have become inevitable in order to dispose of the resulting wastes without harming the environment and human health and to bring them into the economy. In this study, the recovery of sodium-based waste powder soap used in wire drawing processes was carried out. The ion solution method, which is a physical separation method, was used. With this method, the recovery rate was found to be 98%. Thermal and chemical analyzes were carried out with thermogravimetric and differential thermal analyzes device (TGA/DTA), X-ray fluorescence spectrometer device (XRF) and Fourier transform infrared spectroscopy (FTIR) to determine if there is any change in the structure of the material obtained after recovery.

Günümüzde hızla artan tüketimi karşılamak için üretim ve üretime bağlı atık miktarı artmıştır. Ortaya çıkan atıkların çevreye ve insan sağlığına zarar vermeden bertaraf edilmesi ve ekonomiye kazandırılması için geri dönüşüm süreçleri kaçınılmaz hale gelmiştir. Bu çalışmada, tel çekme işlemlerinde kullanılan sodyum bazlı atık toz sabunun geri kazanımı gerçekleştirilmiştir. Fiziksel ayırma yöntemi olan iyon çözelti yöntemi kullanılmıştır. Bu yöntemle iyileşme oranı %98 olarak bulunmuştur. Termogravimetrik ve diferansiyel termal analiz cihazı (TGA/DTA), X-ışını floresan spektroskopisi cihazı (XRF) ve Fourier transform kızılötesi spektroskopisi (FTIR) ile geri kazanım sonrası elde edilen malzemenin yapısında herhangi bir değişiklik olup olmadığını belirlemek için termal ve kimyasal analizler yapılmıştır.
Tel çekme işleminde kullanılan toz sabunun geri kazanımı için filtreleme ve optimizasyon
Keywords: Wire drawing; Die soap; Recovery; Ion solution